USAGE OF HORSE HAIR AS A TEXTILE FIBER AND EVALUATION OF COLOR PROPERTIES - KALAYCI Ece; AVINC Ozan; YAVAS Arzu (Annals of the University of Oradea: Fascicle of Textiles, Leatherwork, 2019)
The usage of horse hair as a textile material can be traced to the old ages. Although many animal hair fibers have lost their importance due to the introduction of synthetic fibers into our lives, special fibers such as horsehair have been able to survive in some unique applications. Horse hair fiber exhibits durability, stiffness, antibacterial, antifungal antiallergic and thermal comfort properties. Horse hair fibers have been used in a wide range of products from surgical sutures to brushes, musical instruments, upholstery fabrics and accessories. It is a promising animal hair fiber especially for technical textiles and special designed products thanks to its prominent textile propertie. The recent studies which are about to usage of horse hair fibers for car seat covers and reinforcement materials for composites prove this claim. Since the application areas of the fibers are mostly visible surfaces, the color of the hair becomes an important parameter. Therefore, the color properties of two different horse hair types (as tail and mane) from two different Arabian horses were examined in this study. Moreover, the structure, properties and the usage areas of horsehair fibers were reviewed in detail and future uses of the horse hair fibers were also discussed.